Determinants of Carbon Emission Disclosure: The Role of Gender Diversity in Moderating Financial and Environmental Factors in Energy Sector Companies - Dwi Sukma Rismahmudah; Hasan Mukhibad (Jurnal Akuntansi Bisnis, 2026)
The issue addressed in this study is the inconsistent empirical findings of prior research regarding the roles of leverage, institutional ownership, and environmental management. Gender diversity is included as a moderating variable to explain the inconsistent research findings.  The sample was selected from energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024, this resulted in 228 firm-year observations. The results indicate that leverage and environmental management significantly affect carbon emission disclosure, whereas institutional ownership shows no significant effect. Furthermore, gender diversity is found to moderate the relationship between the independent variables and carbon emission disclosure. These findings suggest that financial conditions and corporate commitment to environmental management play an important role in enhancing the transparency of carbon emission disclosure. This study contributes to the environmental accounting literature and provides practical insights for improving sustainability reporting practices in Indonesia.